RETRACTED: Stimulating Brand Innovation Strategy via Knowledge Acquisition, Market Orientation, and Strategic Capability Using Social Media Within China’s Online Technology Industry - Yang, Yaliu; Zheng, Xiaowei (Frontiers in Psychology, 2022)
In the context of China's online technology business, this study explores the linkages between knowledge acquisition via social media, two modes of market orientation (proactive and responsive), social media strategic capability, and brand innovation strategy. Data was collected from 853 Chinese technology firms with the help of questionnaire. To analyse the collected data structure equation modelling was applied using smart-PLS 3.3 version. Results indicate that knowledge acquisition from social media, market orientation (proactive, responsive) and strategic capability has significant impact on brand innovation in the context of social media. Furthermore, strategic capability on social media moderates the relationship between knowledge, market orientation (proactive, responsive) and brand innovation in the context of social media. This offers new perspectives on market orientation and brand innovation strategy by extending the literature and testing key assumptions. Moreover, using social media knowledge in social media marketing and innovation management is a sensible approach for making changes and transforming an organization.